Comparison of postoperative complications between different operation methods for esophageal cancer. Issue 8 (27th June 2019) - Ding, Qingqing; Zhou, Wenyin; Xue, Yibo; Han, Xiao; Yin, Dandan; Xue, Lei; Luo, Jinhua
Abstract : Background: We explored the selection of surgical method and differences in postoperative complications in patients with esophageal cancer (EC). Methods: The data of 434 patients with EC who underwent thoracic surgery at the Jiangsu Provincial People's Hospital between January 2011 and December 2016 were collected. Patients were divided into three groups: Sweet surgery (143 cases), Ivor–Lewis surgery (232 cases), and minimally invasive esophagectomy (MIE, 59 cases). The number of postoperative days, number of lymph nodes dissected, and incidence of pulmonary infection, serous membrane fluid, arrhythmia, chylous fistula, gastric emptying dysfunction, and anastomotic leakage were recorded. Results: A statistically significant number of female stage I patients with upper EC underwent MIE ( P < 0.05). Postoperative complications were observed in all three groups but were not statistically significant ( P > 0.05). A greater number of lymph nodes were dissected in the Ivor–Lewis group compared to the other groups ( P < 0.05). Conclusion: Clinically, MIE is often selectively used for women with upper and mid‐early EC, especially in stage I. In our sample, more lymph nodes were dissected in the Ivor–Lewis than in the MIE group, which can reduce recurrence and improve the survival rate. Ivor–Lewis surgery is often used in mid‐lower and terminal EC, while MIE is often used in upper and mid‐early EC. Compared to the other surgical methods, MIE does not increase the risk of postoperative complications. The gradual maturation of MIE technology will further expand indications and increase the number of lymph nodes dissected.